808 nm excited energy migration upconversion nanoparticles driven by a Nd3+–Trinity system with color-tunability and superior luminescence properties. Issue 6 (23rd January 2018) - Guo, Shuai; Tsang, Ming-Kiu; Lo, Wai-Sum; Hao, Jianhua; Wong, Wing-Tak
Abstract : A novel nanostructure is fabricated with an 808 nm excited/Nd 3+ -sensitized EMU system to avoid over-heating effects, gained with favourable luminescence properties. Abstract : We have developed energy migration upconversion (EMU) nanoparticles (UCNPs) with optimal Nd 3+ -sensitization under excitation of an 808 nm laser to avoid over-heating effects caused by a 980 nm laser while maximizing the excitation efficiency. To realize efficient 808 nm sensitization, a "Nd 3+ –Trinity system" was implemented in the energy migration upconversion (EMU) cores (NaGdF4 :Yb, Tm@NaGdF4 :Yb, X, X = Eu/Tb), resulting in a core–multishell structure of EMU cores (accumulation layer@activation layer)@transition layer@harvest layer@activation layer. The spatially separated dopants and optimized Yb 3+ /Nd 3+ content effectively prevented severe quenching events in the UCNPs and their Nd 3+ -sensitized EMU-based photoluminescence mechanism was studied under 808 nm excitation. These Nd 3+ –Trinity EMU system UCNPs presented enhanced upconversion luminescence and prolonged lifetime compared to the 980 nm excited UCNPs of the EMU system. It is proposed that 975 nm and 1056 nm NIR photons induced from the Nd 3+ → Yb 3+ energy transfer facilitate the Tm 3+ accumulation process due to the matched energy gaps, which contributes to the extended lifetimes. More importantly, the synthesized UCNPs had a small average size of sub-15 nm and they not only exhibited color-tunability via Eu 3+ /Tb 3+ activators, but also released a larger portion of Tm 3+ red emission at 647 nm and had better penetration ability in water under 808 nm excitation, which are favorable for bioimaging applications.